ANTIBIOTIC THERAPY FOR ENT INFECTIONS - A. B. Turovsky; Yu. A. Karyuk; V. V. Kondrashina (Klinicist)
The paper outlines basic principles of and new approaches to antibiotic therapy for ENT and upper respiratory tract infections, from point of view of the authors, on the basis of the data available in Russian and foreign literature.